Gestational Weight Gain: Results from the Delta Healthy Sprouts Comparative Impact Trial - Jessica L. Thomson; Lisa M. Tussing-Humphreys; Melissa H. Goodman; Sarah E. Olender (Journal of Pregnancy)
Introduction. Delta Healthy Sprouts trial was designed to test the comparative impact of two home visiting programs on weight status, dietary intake, and health behaviors of Southern African American women and their infants. Results pertaining to the primary outcome, gestational weight gain, are reported. Methods. Participants (n=82), enrolled early in their second trimester of pregnancy, were randomly assigned to one of two treatment arms. Gestational weight gain, measured at six monthly home visits, was calculated by subtracting measured weight at each visit from self-reported prepregnancy weight. Weight gain was classified as under, within, or exceeding the Institute of Medicine recommendations based on prepregnancy body mass index. Chi-square tests and generalized linear mixed models were used to test for significant differences in percentages of participants within recommended weight gain ranges. Results. Differences in percentages of participants within the gestational weight gain guidelines were not significant between treatment arms across all visits. Conclusions. Enhancing the gestational nutrition and physical activity components of an existing home visiting program is feasible in a high risk population of primarily low income African American women. The impact of these enhancements on appropriate gestational weight gain is questionable given the more basic living needs of such women. This trial is registered with ClinicalTrials.gov NCT01746394, registered 4 December 2012.